THE ETHICAL CHALLENGES OF RECOVERING HISTORICAL MEMORY SEEING LAND: RESITUATING LANDSCAPES THROUGH CONTEMPORARY INDIGENOUS ART EXHIBITIONS - Robertson, Carmen (Les ateliers de l'éthique / The Ethics Forum, 2019)
Canadian landscapes on gallery walls in art museums serve as a primer for understanding the nation. Visitors cannot easily escape the purposeful emptiness of rugged scenes meant to visually assure them of the nation’s right to colonial possession. Most viewers respond positively to these pretty pictures because such ways of seeing the art history of Canada has been naturalized and normalized, appearing politically neutral.Ubiquitous Canadian landscape paintings also reinforce colonial claiming of land and authorize erasure of Indigenous relations with the land. Understanding the noted landscapes as something other than part of a national narrative, however, has not been widely accepted, even as a sanctioned mandate to broaden art historical narratives has resulted in displaying additional Indigenous art in galleries. In an analysis that considers ways to re-vision the privileged colonial narrative present in Canadian art museums, deeper ethical issues arise in relation to institutional structures. Here the analysis focuses on three projects in and around Canada 150, including examples such as Shame and Prejudice: A Story of Resilience (2017–2020, Kent Monkman), the rehanging of Norval Morrisseau’s Artist and Shaman between Two Worlds (1980) at the National Gallery of Canada, and the Michael Belmore and A. J. Casson: Nkweshkdaadiimgak Miinwaa Bakeziibiisan/Confluences and Tributaries exhibit at the Ottawa Art Gallery (2018, Ottawa). This essay explores questions regarding whether ways of seeing land differently come about simply by hanging Indigenous art on institutional walls or whether more systemic change is required.